Synthesis and evaluation of pyrrolobenzodiazepine dimer antibody-drug conjugates with dual β-glucuronide and dipeptide triggers - Gregson, Stephen J.; Barrett, Allison M.; Patel, Neki V.; Kang, Gyoung-Dong; Schiavone, Davide; Sult, Erin; Barry, Conor S.; Vijayakrishnan, Balakumar; Adams, Lauren R.; Masterson, Luke A.; D'Hooge, Francois; Snaith, Mike; et al. (European journal of medicinal chemistry, 2019)
Antibody-drug conjugates (ADCs) containing pyrrolobenzodiazepine (PBD) dimers are currently being evaluated in human oncology clinical trials with encouraging results. To further improve the therapeutic window, next-generation PBD drug-linker design has focused on the inclusion of additional tumor-selective triggers and use of lower-potency PBDs. β-Glucuronidase is a well-known target for discovery prodrugs due to increased presence in tumor cells and microenvironment. In this study, a β-glucuronidase cleavable cap was investigated at the PBD N10-position and compared with corresponding free imine ADCs. SG3600 (glucuronide) ADCs showed in vitro and in vivo efficacy/tolerability comparable to SG3400 (imine) ADCs, and good 50% inhibitory concentration differentials were observed in vitro between control non–antigen-targeted ADCs and targeted ADCs. Dependence on β-glucuronidase for SG3600 activity was demonstrated through CRISPRCas9 knockdown studies and addition of exogenous β-glucuronidase. SG3600 showed better serum stability, improved conjugation efficiency and was able to reach high drug-to-antibody ratio without aggregation. [Display omitted] •β-glucuronidase cleavable cap maintained efficacy for targeted antibody-drug conjugates.•Antibody-drug conjugate format essential for activity of the β-glucuronide derivative.•β-glucuronidase CRISPR knockdown renders β-glucuronide antibody-drug conjugates inactive.•Conjugation of β-glucuronide to high drug-to-antibody ratio was possible without aggregation.•Serum stability improved for trastuzumab-C239i-β-glucuronide compared to imine conjugate.